1993
DOI: 10.1557/jmr.1993.2774
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Y2BaCuO5 particles on the growth morphology of peritectically solidified YBa2Cu3O7−x

Abstract: Modifications of a recent model by Izumi et al. 1 on diffusion controlled growth of YBa 2 Cu 3 07x (123) superconductors are proposed, taking into account especially the engulfment process of the Y 2 BaCuOs (211) particles into the solidifying 123 interface. The proposed modifications are evidenced by experimental results and applied to explain microstructural features of the 123 superconducting material. In particular, the 1:1 correlation between 123 platelet thickness (planar defect spacing) and 211 particle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

1993
1993
1998
1998

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(28 citation statements)
references
References 10 publications
0
28
0
Order By: Relevance
“…27,35,36 Planar growth stability theory 37,38 and computer simulations of the yttrium concentration distribution around 211 particles 39 have been applied on the length scale of formation of the dendrites observed in the present study (i.e., over dimensions of a few microns). Such a process has been reported by other authors, albeit on a different scale.…”
Section: Resultsmentioning
confidence: 99%
“…27,35,36 Planar growth stability theory 37,38 and computer simulations of the yttrium concentration distribution around 211 particles 39 have been applied on the length scale of formation of the dendrites observed in the present study (i.e., over dimensions of a few microns). Such a process has been reported by other authors, albeit on a different scale.…”
Section: Resultsmentioning
confidence: 99%
“…For example, 211 grains which are entrapped in the solidification front influence the microstructure of melt-textured 123. 26,27 Hence their orientation could compete with the general growth direction and could induce secondary nucleation, another factor inducing deviation with respect to the imposed gradient. However, in the present case there is no orientation of 211 trapped grains, this is in fact rather natural as a thermal gradient itself has no energy to orient particles except perhaps through convective forces.…”
Section: A Texturing 211: Unfavorable Parametersmentioning
confidence: 99%
“…Nevertheless, these interactions seem to be relevant for the growth of the 123 system. In fact, Schmitz et al [23] have shown that some 123 bridges tend to be formed between the solidifying front and the neighbouring 211 particles. We stress here that bridge formation could be anisotropic along the a-b planes.…”
Section: Origins Of the Pattern Formationmentioning
confidence: 99%